2019
DOI: 10.3934/publichealth.2019.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer screening: Understanding the health literacy needs of hispanic rural residents

Abstract: Purpose Hispanics residing in rural areas are among those who are least likely to be screened for colorectal cancer (CRC) and more likely to present with late stage CRC than other racial or ethnic groups. We conducted a pilot study utilizing a mixed-method approach to explore perceptions of CRC and CRC screening among Hispanic adults residing in South Texas rural communities and to identify health literacy needs associated with CRC screening uptake. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Concerning citations, a V-size distribution can be observed for most policy documents, obtaining a significant counting frequency for studies with low <1–2> and high <12–15> numbers of citations. Regarding the strength of evidence, studies with case study and qualitative research design [1] , as well as descriptive ones [2] were more frequent within the cited studies than the experimental studies [4] and systematic reviews with meta-analysis [5] (see Figures 1 and 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning citations, a V-size distribution can be observed for most policy documents, obtaining a significant counting frequency for studies with low <1–2> and high <12–15> numbers of citations. Regarding the strength of evidence, studies with case study and qualitative research design [1] , as well as descriptive ones [2] were more frequent within the cited studies than the experimental studies [4] and systematic reviews with meta-analysis [5] (see Figures 1 and 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, there are limitations and gaps in these policies, such as the need for funding, clear goals, and evaluation of policy implementation [3] . For example, the education sector plays a crucial role in achieving health literacy goals, as health literacy can be obtained and used across various settings, including schools [4] , [5] . Despite recognizing its importance, health literacy must be more included as an agenda item in education policies [6] .…”
Section: Introductionmentioning
confidence: 99%
“…In light of these findings, it is unlikely that participants with low health literacy, as well as those with excellent health literacy, will exhibit high levels of participation in cancer screening. Indeed, previous research has indicated that individuals with poor health literacy are less likely to adhere to colorectal screening, presenting a significant barrier to their participation in screening initiatives [6,45].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the healthcare delivery system in rural areas is still under constant development and reform adjustment, with lower accessibility and fewer quality resources ( Cai et al, 2021 ) and a weaker environment still in need of improvement ( Kozhimannil and Henning-Smith, 2021 ). In contrast, the new rural cooperative medical insurance introduced in China has led to changes in the budget constraints of rural households, influencing the economic resources, living arrangements, and care patterns of rural residents ( Wittich et al, 2019 ), which has had some positive effects on their health status, but is far from adequately meeting the high level of demand for quality healthcare resources in rural areas ( Cheng et al, 2018 ). In addition to further improving healthcare conditions in rural areas, strengthening the social security system in rural areas, and achieving full coverage of county and rural healthcare institutions ( Li et al, 2021 ), policy options for achieving health poverty alleviation in rural areas could also start with improving income inequality ( Sun et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%